2007
DOI: 10.1152/ajpheart.01195.2006
|View full text |Cite
|
Sign up to set email alerts
|

Mediating δ-opioid-initiated heart protection via the β2-adrenergic receptor: role of the intrinsic cardiac adrenergic cell

Abstract: Uretsky BF. Mediating ␦-opioid-initiated heart protection via the ␤ 2-adrenergic receptor: role of the intrinsic cardiac adrenergic cell. Am J Physiol Heart Circ Physiol 293: H376-H384, 2007. First published March 16, 2007; doi:10.1152/ajpheart.01195.2006.-Stimulation of cardiac ␤ 2-adrenergic receptor (␤2-AR) or ␦-opioid receptor (DOR) exerts a similar degree of cardioprotection against myocardial ischemia in experimental models. We hypothesized that ␦-opioid-initiated cardioprotection is mediated by the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
33
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 32 publications
7
33
1
Order By: Relevance
“…Our results strongly support the existence of DORs in the mammalian heart by the identification of DOR mRNA, receptor protein, and membrane-associated binding sites in the rat heart atria. This is in line with recent Western blot analyses identifing DOR-IR bands in left ventricular cardiomyocytes of hamsters (Bolte et al, 2009) or in intrinsic cardiac adrenergic cells of rats (Huang et al, 2007). In addition, [ 3 H]diprenorphine binding sites in cultured cardiomyocytes were displaced by unlabeled DOR-(DPDPE) selective ligands, indicating the presence of DORs (Zimlichman et al, 1996).…”
Section: D-opioid Receptors In the Developing Rat Heartsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results strongly support the existence of DORs in the mammalian heart by the identification of DOR mRNA, receptor protein, and membrane-associated binding sites in the rat heart atria. This is in line with recent Western blot analyses identifing DOR-IR bands in left ventricular cardiomyocytes of hamsters (Bolte et al, 2009) or in intrinsic cardiac adrenergic cells of rats (Huang et al, 2007). In addition, [ 3 H]diprenorphine binding sites in cultured cardiomyocytes were displaced by unlabeled DOR-(DPDPE) selective ligands, indicating the presence of DORs (Zimlichman et al, 1996).…”
Section: D-opioid Receptors In the Developing Rat Heartsupporting
confidence: 90%
“…Consistently, Western blot analysis in P1 and P7 and adult rat heart atria also revealed that cardiac DOR proteins significantly increased from the first day of birth toward adulthood. In parallel, the number of membrane-associated DOR-specific binding sites increased, further substantiating existing evidence (Huang et al, 2007;Deo et al, 2008;Bolte et al, 2009). Taken together, our findings of DOR mRNA, receptor protein, and membrane binding sites strongly support the existence of rat cardiac DORs already at birth, with a gradual increase in expression toward adulthood.…”
Section: D-opioid Receptors In the Developing Rat Heartsupporting
confidence: 88%
“…Canine right atrial and sinus node tissues were obtained from mixed-gender adult (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) kg) mongrel dogs. The Institutional Animal Care and Use Committee, in compliance with the National Institutes of Health Guide for the Care and Use of Laboratory Animals, approved all procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The location of the responsible receptors remains undefined, but studies in vitro (21,27,35,39) support the widely held presumption that postjunctional DORs are involved. Intrinsic adrenergic cells, cardiomyocytes, adipocytes, fibroblasts, and resident leukocytes are all potential sites for nonneural DORs (21,27,29,35).…”
mentioning
confidence: 96%
See 1 more Smart Citation